Analisis Pengendalian Kualitas Sapu Nilon Menggunakan Metode Six Sigma - Frastiyo, Riski; Wahid, Abdul (Metode : Jurnal Teknik Industri, 2024)
In the era of globalization, business competition and producers to further spur productivity and creativity in running a business, products must be of high quality and be able to adapt to market changes. CV. Unit Clean Industry is a manufacturing company engaged in the distribution of household cleaning equipment. Company CV. The Clean Industry Unit in carrying out the production process of nylon brooms has many discrepancies in the products produced. So the researchers applied the six sigma method as a proposed improvement to the defective nylon broom product that occurred in the company. The purpose of this study is to identify defective products using the six sigma method, determine the most dominant causes of defects using Six Sigma. The Six Sigma method itself has 5 stages, namely Define, Measure, Analyze, Improve, Control. The results of the calculation of the six sigma method are obtained, namely an average sigma level of 3.00 with a possible damage of 70,430 for a million times of production (DPMO). Where the cause of the defective product is damage to the damaged lakop hole, broken lakop and broken lakop frame. This is of course the cause of enormous losses if left untreated. Then it is necessary to take actions such as periodic maintenance and repair of machines, supervising employees who work in the production section to improve the quality of the goods produced and record the production results of each type of machine and the types produced by employees during the production process.